Global Voices in Education Ruth Wong Memorial Lectures - Tan, Oon Seng.; Seng, Seok Hoon.; Wong, Hee Ong.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This book brings together selected lectures given by eminent educationalists in memory of Ruth Wong, an influential figure in the field of education. The lectures represent the powerful ideas seeded by Dr Wong and address the challenges of education in Singapore$1 (Bs journey from a textbook case of poor education to a world-class educational system. The educational standard that we enjoy today was only possible thanks to visionary thinking and missionary zeal. This collection addresses key themes and issues in learning, schooling, teaching, teacher education, educational research and policy innovation, making it a must-read for educators, educational leaders and policy makers interested in providing uplifting education for the next generation of learners.s
1 Prologue -- 2 Introduction -- 3 Some thoughts about teaching and learning -- 4 The concept of educational disadvantage and some implications for the classroom teacher -- 5 Utilization of new knowledge and application of new ideas in education: A discussion of the vitalization of education as a profession and discipline -- 6 Education and the changing economic and industrial order: An international perspective -- 7 Research and the improvement of teaching -- 8 Recent conceptions of children's learning: Implications for classroom practice -- 9 Measuring and monitoring educational achievement -- 10 Engaging children's minds: innovative research and practice -- 11 A personal philosophy of education -- 12 The professional education of teachers -- 13 The timeless teacher: Contemporary research and ancient models -- 14 The value of principled eclecticism in education reform: 1965 and 2005 -- 15 Schooling today: Teaching competence, creativity and compassion -- 16 Mediated learning experience (MLE) strategies and children's cognitive plasticity -- 17 Epilogue.
Keywords: Education; School management and organization; School administration; Educational policy; ducation and state; Teaching; Education; Educational Policy and Politics; Administration, Organization and Leadership; Teaching and Teacher Education; Electronic books